Performance of an agricultural engine using mineral diesel and ethanol fuels - Farias,Marcelo Silveira de (2017)
ABSTRACT: The global demand for alternatives for mineral diesel oil is growing due to the need for satisfying sustainability and environmental requirements, forcing industries and research institutions to develop new alternative fuels. The objective of this study was to evaluate the performance parameters of an agricultural engine using two different fuels: mineral diesel oil and ethanol. The experiment was conducted on a dynamometric stand using two engines for agricultural use but with a modified fuel injection system, suitable for both diesel and ethanol, in the speed range 1200-2300rpm. The performance of the engines was analyzed considering the power take-off from the tractors for each fuel, as established in the standard NBR ISO 1585. The data obtained showed that at the working speed that provides 540rpm at the power take-off, the engine performance changed when powered by ethanol, with a reduction in the maximum power and increased specific fuel consumption.